The search for the social Role of the Teacher - Tellez Fajardo, Alicia; Nieves Tavera, Marlen María (Rastros Rostros, 2013)
This article is the result of over ten years of studies conducted by the Pedagogy and Languages group inthe Faculty of Education at the Bucaramanga campus of Universidad Cooperativa de Colombia. The aim of the text is to review the history of teacher training, from its beginnings during General Santander’s government in the early 19th century, until the end of the 20th century. Its evolution is shown through different governments, according to their vision of education, and, naturally, emphasizing the idea of the teacher’s social role. This focus on the social role arises out of the search for clues in the training of teachers with the ability to orient educational policies centered on research in order to generate knowledge and creative development, without neglecting solidarity, and with the end goal of meeting current requirements. Eight historical moments in the country’s teacher training are presented. Currently, efforts are being made to maintain research as part of teacher training, and to ensure that the pedagogy is accorded an importance that matches the social responsibility demanded by society.
Keywords: teacher; pedagogy; social role; pedagogical knowledge